Callus induction in cotyledons of Moringa oleifera lam - Nieves, Mylene C.; Aspuria, Evalour T. (2011)
Callus cultures of Moringa oleifera Lam. were successfully established from cotyledon explants obtained from green mature seeds. Benzyladenine (BA) alone (2.5 mg L -1) significantly increased callus formation but was not significantly different when combined with increasing levels of 2,4-dichlorophenoxyacetic acid (2,4-D) (1.0-5.0 mg L -1) and further supplemented with thidiazuron (TDZ). Loose crystalline calli were observed in media containing 2,4-D and BA singly or in combination, while compact, nodular and loose calli were obtained when the culture media were further enriched with TDZ. BA and 2,4-D singly or in combination did not significantly enhance degree of callus formation but BA in combination with 1.0 and 5.0 mg L -1 2,4-D and TDZ significantly increased degree of callusing. A significant increase in callus weight was observed in BA at different levels combined with 2,4-D (1.0 and 2.5 mg L -1). Addition of TDZ to BA and 2,4-D containing media further increased callus weight. Slight greening of calli was observed 4 wk after the first transfer onto the shoot induction media; however, statistical analysis revealed that there was no significant difference among treatments. Microscopic observation of hand-sectioned protrusions on green calli revealed heterogenous and asynchronous cell growth showing actively dividing cells. Xylem differentiation was also evident, indicating initiation of bud initials.
Keywords: Moringa oleifera